(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: We research the topic intending to determine the current situation and some factors affecting the patient safety attitude (PSA) of the medical staff (MS) at Ninh Binh Provincial General Hospital year 2021. Methods: We conducted a cross-sectional study on 343 randomly selected MS currently working in Ninh Binh Provincial General Hospital from November 2021 to December 2021. The study used the abridged SAQ scale 2006 from the University of Texas to measure PSA. We used OR, 95% CI, to determine the relationship between PSA and some related factors among MS. Results: MS have the highest percentage and average score on PSA in the item "Job satisfaction" (75.8%, 4.0 ± 0.6) and "Conditions working" (62.97%, 3.8 ± 0.6). MS with a post-graduate qualification had a PSA score 6.8 times higher (95% CI: 1.8 - 25.6) than their qualified counterparts. Specialization is University. In addition, contracted MS had a 3.6 times higher PSA (95% CI: 1.4 - 9.2) than regular MS. Conclusion: Research has shown that hospitals should focus on continuous training to reinforce PSA of MS, especially those with university degrees.